The adoption and effect of artificial intelligence on human resources management - Tyagi, Pallavi; Chilamkurti, Naveen, 1974-; Grima, Simon; Sood, Kiran; Balusamy, Balamurugan (Emerald studies in finance, insurance, and risk management, 2023)
Emerald Studies In Finance, Insurance, And Risk Management 7 explores how AI and Automation enhance the basic functions of human resource management. The traditional framework of Human Resource Management (HRM) primarily consists of four functions: Human Resource Planning, Recruitment and Selection, Training and Development and Performance Management Systems which help businesses in hiring, motivating and retaining employees. The introduction of Artificial Intelligence (AI) has changed all of these aspects. This second volume in The Adoption and Effect of Artificial Intelligence on Human Resources Management Series reflects upon: the accuracy of using AI to nominate candidates; the change readiness of employees; impacts and challenges on HRM practices; effects on upskilling; and the effects of the pandemic; concluding with an overall state of industry trends. This book is ideal for HR managers, senior managers, researchers, and students planning a career in this field.